Endotoxemia in Peritoneal Dialysis Patients: A Pilot Study to Examine the Role of Intestinal Perfusion and Congestion. Issue 1 (January 2017) - Grant, Claire; Harrison, Laura; Hoad, Caroline; Marciani, Luca; Cox, Eleanor; Buchanan, Charlotte; Costigan, Carolyn; Francis, Susan; Lai, Ka-Bik; Szeto, Cheuk-Chun; Gowland, Penny; McIntyre, Christopher
Endotoxemia is common in advanced chronic kidney disease and is particularly severe in those receiving dialysis. In hemodialysis patients, translocation from the bowel occurs as a consequence of recurrent circulatory stress leading to a reduction in circulating splanchnic volume and increased intestinal permeability. Peritoneal dialysis (PD) patients are often volume expanded and have continuous direct immersion of bowel in fluid; these may also be important factors in endotoxin translocation and would suggest different therapeutic strategies to improve it. The mechanisms leading to endotoxemia have never been specifically studied in PD. In this study, 17 subjects (8 PD patients, 9 healthy controls) underwent detailed gastrointestinal and cardiac magnetic resonance imaging during fasted and fed states. Gross splanchnic perfusion was assessed by quantification of superior mesenteric artery flow. Magnetic resonance imaging findings were correlated to endotoxemia, markers of hydration status and cardiac structure and function.